Investigation study of various carrier type for air tunnel transportation - Shibani, Wanis Mustafa Edukali (2018)
This study highlights the influences of internal airflow on the motion of carrier in an air tunnel. The aim of this work is to study an alternative method of transporting goods from one place to another through an air tunnel. The development of such transport system can help to reduce traffic jams and deliver goods faster to its desired places. The analysis of carrier movement and the flow surrounding it was performed using FLUENT software version 16.1. The computational domain along the air tunnel was discretized using tetrahedron grids. The adopted numerical scheme was the time-averaged Navier-Stokes equation with turbulence modeling and the scheme was solved using the SIMPLE algorithm. The air movement was created by the presence of pressure difference. The results indicate the possibility of defining a carrier, which has a particular geometry to float and move. This study was performed in three stages. The first stage started with the investigation of suitable geometry of the carrier. Four shapes were considered, i.e. box, ball, wedge A and wedge B shape. The wedge A and B had the same configurations and dimensions, but the only difference was the position of each shape, facing the inlet in the air tunnel. It was found that the wedge B and the box shape had the fastest speed compared to the other two shapes. Rectangular wings with a cross section of either FX63-137, NACA 0012 or NACA 4412 airfoil was selected for this study. In the second stage, a carrier in a box shape with three rectangular wings attached was investigated. In the last stage, the carrier in wedge B shape with wings attached was examined. The results indicate that the carrier equipped with the airfoil NACA0012 has better performance than the carrier that uses airfoil FX 63-137 or airfoil NACA 4412 at wind speed of 30.8 m/s. In the experimental testing, a carrier in a box shape with wings attached was assessed. The result reveals that the movement of the carrier (FX63-137) shows better performance at the wind speed of 19.6 m/s, and this result is consistent with the simulation result.